Absorption Ability Of Inclusion School Students In Number Counting Operations - Sakdiyah, Ismi Halimatus; Murtinasari, Frida (Yana Research, 2023)
The aim of this research is to determine the absorption capacity of Jember TPA Inclusion Middle School students after being given additional lesson hours on number counting operations material. This type of research is qualitative with a descriptive approach. The research subjects were students in classes V11, V11 and 1X of Jember TPA Inclusion Middle School. The instruments used were field notes, tests of students' ability to absorb number calculation operations and interviews. The results obtained were student absorption capacity of 67% and classical completion 35%, because classical completeness is lower than the absorption capacity, classically it is said to be incomplete, meaning that you have to repeat the previous KD even though there are several students who have completed it, so it can be said that the students' absorption capacity in number counting operations is said to be very low.